Implementasi Sistem Pembayaran Quick Response Indonesia Standard Bagi Perkembangan UMKM di Medan - Josef Evan Sihaloho; Atifah Ramadani; Suci Rahmayanti (Universitas Pendidikan Nasional, 2020)
ABSTRACTThe use of server-based electronic money is one of the most popular non-cash payment systems in use today. The form of server-based electronic money is e-wallet / digital wallet. E-wallet can be used to transact by customers, if the merchant provides an application Same e-wallet to customers. This made Bank Indonesia, as the regulator of the payment system, issue a new payment channel namely; QRIS (QR Code Indonesia Standard). The use of QRIS is used to standardize all e-wallets applications that use the QR Code system to conduct payment transactions. This study examines how the application of QRIS to UMKM in Medan, and describes the roles, constraints, and income of UMKM s in the presence of QRIS. The research method used is interviews and literature studies with UMKM traders who have used QRIS as a payment tool in their characters. This research indicates that QRIS has benefits for UMKM traders.